Unmasking the Enigma: Influenza Vaccine and the Rare Case of Post-Vaccination Pericarditis - Ekrem Yetiskul; Alaukika Agarwal; Gaetano Di Pietro; Faris Qaqish; Salman Khan; Shahkar Khan (Case Reports in Infectious Diseases)
Acute pericarditis is an inflammatory condition involving the pericardium, the double-layered sac that surrounds the heart. It is characterized by chest pain, typically pleuritic and sharp, along with other clinical and laboratory findings indicative of pericardial inflammation. While acute pericarditis following influenza vaccination is rare, it has been reported in medical literature. The relationship between vaccinations, including the influenza vaccine, and pericarditis is particularly interesting, as it has implications for public health and vaccination programs. Understanding the pathophysiological mechanisms behind vaccine-induced pericarditis and recognizing the clinical presentation are essential for healthcare professionals to diagnose, manage, and educate patients appropriately.